Strategic Ambiguity and Power Projection in Indo-Pacific Region: : A Perspective of U.S.A and China - Ahmed, Foisal; Rahman, Md. Sohanur (The Jahangirnagar Review, 2025)
The Indo-Pacific area has become a crucial point in current global politics. The region handles one-third of global trade and a large portion of seaborne oil shipments. The Indo-Pacific region has become very important at present because the United States wants to dominate here and China wants to present itself as the superpower of Asia, for this reason, the two superpowers are busy strengthening their teams. Here, they are attracting small countries to their team in various ways. They adopt methods like strategic ambiguity and power projection to attract small countries to their team, so knowing their methods in depth is very important for this region and the whole world. We can see from reviewing previous studies that the superpowers who are using strategic ambiguity as a tool to dominate or benefit themselves have not been explained or reviewed in depth. So, through this research, we will explore how the United States and China are dominating this region and what their strategies are, how they use strategic ambiguity as their tool. The methodology used is a qualitative method, and most of the information is taken from secondary sources such as various articles, books, journals, and publications. We can see here that the United States is creating various groups in this region to challenge China and maintain its dominance, while China is strengthening itself in various ways by creating new weapons and sometimes through economic policies. From the findings here, we see how the US and China are using small states to put them in a dilemma. So small states should be careful in this regard and maintain their own identity. Moreover, the paper is very important to understand in depth how the United States and China use small countries in this region to maintain their dominance and for their economic development. Along with that, small countries will know what they should do or what policies they should take. This paper will serve as an eye-opener for them.